Sistem Informasi Monitoring Kenderaan Pengangkut Sampah di Kabupaten Gorontalo - Trias Saputra Singo; Muhammad Rifai Katili; Sitti Suhada (Gorontalo State University, 2021)
Environmental And Natural Resource Agency remains experiencing a problem related to waste hauling from Temporary Waste Disposal Site (TPS) To Final Disposal Site (TPA). In addition, people living nearby the site complain about certain things such as workers cross by the garbage dump with piling up waste, workers haul the waste at an irregular time as determined, and workers take the wrong route incidentally based on their own reason. Objective of this research was to create a web-based apps system which could monitor trash hauling from Temporary Waste Disposal Site (TPS) to Final Disposal Site (TPA) in area of Limboto Sub-district, Gorontalo District. It was designed by applying prototype system development method. Result of research showed that the created waste Collection Vehicle Monitoring Information System in Gorontalo District could optimize search process for garbage dump provided by gorontalo district government.